The Influence of Store Atmosphere, Social Media, Word of Mouth, and Price on Purchase Intention of MSME Consumers - Deby R. Karundeng; Musran Munizu; Tengku Kespandiar; Dhety Chusumastuti; Miko Andi Wardana (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study set out to examine how social media, word-of-mouth, shop ambiance, and pricing impacted consumers' choice to buy. Research of this kind is quantitative. Primary data collected from a sample of patrons at a restaurant in one city in Indonesia district served as the research's data source. By delivering questionnaires to 100 customers, accidental sampling was used to acquire the data. The multiple regression analysis approach is employed in this investigation. The results of this investigation suggest that social media significantly influences how consumers make purchases. Word of mouth plays a vital role in how consumers decide which products to buy. The environment of the store has a big impact on how consumers decide what to buy. The purchase decision-making process for consumers is significantly influenced by price. Social media, word-of-mouth, the environment in the shop, and pricing all have a big impact on how consumers decide what to buy.